ChemInform Abstract: Synthesis of Functionalized trans‐A2B2‐Porphyrins Using Donor—Acceptor Cyclopropane‐Derived Dipyrromethanes. Issue 38 (30th August 2013) - Beyzavi, M. Hassan; Nietzold, Carolin; Reissig, Hans‐Ulrich; Wiehe, Arno
Abstract Compound VIII is synthesized in 6 reaction steps.